Australia - Gitlin, Marty (Minneapolis, MN : Bellwether Media, 2018)
A brief overview of Australia, discussing its social life, wildlife, government and more.
The amazing rock -- Location -- Landscape and climate -- Wildlife -- People -- Community life -- Customs -- School and work -- Play -- Food -- Celebrations -- Timeline -- Fast facts -- Glossary.
Includes bibliographical references (page 31) and index.
6.6
3-6
810L
Keywords: Australia -- Juvenile literature; Australia